PT FWD Insurance Indonesia's Creative Team's Strategy in Conducting In-House Production on Vodcast Blak blakan Content on Youtube - Fajar Muttaqin; Vivien Febri Astuti (Journal of Communication Studies, 2026)
This study discusses the in-house production strategy implemented by the creative team of PT FWD Insurance Indonesia in the production of Vodcast Blak Blakan content on YouTube. The research uses a descriptive qualitative approach with data collection methods through in-depth interviews and active participation. Active participation is carried out by being directly involved in every stage of the production process, starting from content planning (pre-production), the process of shooting (production), to the process of editing and distributing content (post-production). The object of this research is the creative team of PT FWD Insurance Indonesia, especially those involved in the implementation of in-house production strategies. The results of the study provide a detailed overview of the in-house production strategies implemented, ranging from content planning, recording process, editing, to content distribution. The findings of this study show how each stage of production is carried out internally by the creative team so as to result in an integrated and efficient work process. In addition, this study also presents a SWOT analysis as a tool to map the strengths, weaknesses, opportunities, and threats of the in-house production strategy that has been implemented by PT FWD Insurance Indonesia